Influence of Accelerated Ageing on Total Soluble Seed Protein Profiles of Tomato - K. VISHWANATH; K.P.R. PRASANNA; RAME GOWDA; S. RAJENDRA PRASAD; S. NARAYANASWAMMY; H.M. PALLAVI (Seed Research, 2026)
Study was conducted to compare 0 to 9 days accelerated aged seed lots of tomato with germination and vigour index that varied from 92 to 0 and 1210 to 0, respectively. Germination loss became more accentuated with increase in time of ageing. Total soluble seed protein banding pattern of different aged seeds revealed that there has been decline in band intensity, band numbers or disappearance of some bands as period of ageing advanced. However, no much variation was observed up to three days of ageing (ie. up to 41 % of germination). Thus, seed lots with slight variation either in germination or vigour could also be used for varietal characterization by SDS-PAGE to differentiate the cultivars or even for genetic purity testing, but not the seed lots which are severely aged that lost threshold limit of 50 per cent.